29th AIAA Applied Aerodynamics Conference 2011
DOI: 10.2514/6.2011-3028
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of Pitch Damping Stability Derivatives for Finned Projectiles

Abstract: The pitch damping dynamic stability derivatives were predicted for two basic finned projectiles using two distinct numerical techniques, namely, the transient planar pitching method and the steady lunar coning method. The dependence of these methods on various aerodynamic and numerical modeling parameters is presented. The accuracy of these methods is also compared to free-flight experimental data for Mach numbers in the range 0.5-4.5. Both numerical methods yielded comparable results, except for some transoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Owing to the angle of attack limitation of the pitch decay approach an effort was undertaken using the forced oscillation approach. [10][11][12][13][14] Forced oscillation results are shown for the Mach 2.48 ANF configuration with the CG located at 6 calibers from the nose in Figure 8. Here the effect of reduced frequency and number of points per cycle were examined to determine which frequency should be used for future analysis on this geometry and others near these conditions.…”
Section: A Army-navy Finner Low Alpha Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the angle of attack limitation of the pitch decay approach an effort was undertaken using the forced oscillation approach. [10][11][12][13][14] Forced oscillation results are shown for the Mach 2.48 ANF configuration with the CG located at 6 calibers from the nose in Figure 8. Here the effect of reduced frequency and number of points per cycle were examined to determine which frequency should be used for future analysis on this geometry and others near these conditions.…”
Section: A Army-navy Finner Low Alpha Resultsmentioning
confidence: 99%
“…[10][11][12][13][14]16 In this approach the geometry is forced to undergo a specified sinusoidal motion around the angle of attack of interest. The equations of motion for the forced oscillations are given in Eqns.…”
Section: Forced Oscillation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,13,14,15 In the current effort, the total normal force and pitching moment are assumed to have the functional dependence consistent with a linear force and moment expansion. When simplified for the case of planar pitching motion (i.e.…”
Section: Transient Planar Pitching Simulationsmentioning
confidence: 99%
“…Current advances in the maneuverability of projectiles necessitate accurate dynamic stability predictions at high angles of attack. Most experimental 1-6 and numerical [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] studies have successfully demonstrated the ability to obtain the dynamic stability derivatives at zero angle of attack for a range of projectiles and flight conditions. This study seeks to extend current advanced numerical techniques to predict dynamic stability derivatives, in particular the roll damping and Magnus derivatives, at angles of attack up to 90° for fin-stabilized projectiles.…”
Section: Introductionmentioning
confidence: 99%